Praktik Bermusik Musisi Muda dalam Skena Metal Ekstrem - Oki Rahadianto Sutopo; Agustinus Aryo Lukisworo (Universitas Negeri Malang, 2020)
This article investigates the young extreme metal musicians’ musical practices in Yogyakarta within the context of neoliberal era. To construct an empirical knowledge based on young extreme metal musicians’ narratives, this research utilized qualitative approach, specifically ethnography, from April to August 2019. In order to articulate conflictual and hierarchical dimension of extreme metal scene, this research applied Bourdieusian perspective. Based on data analysis, this study shows that, firstly, objectively, young musicians’ practices started within the condition which social inequality already existed. This represent a hierarchical characteristic of extreme metal scene as a field of struggle -ranging from local, national, to global level. Secondly, theoretically, young musicians’ practices within extreme metal scene require and reproduce particular capital, with regard to the specific rule of the game of the extreme metal scene, defined as extreme metal capital. Thirdly, the goal of the extreme metal, social, and symbolic capital accumulation, also cultural codes embodiment, was on the extreme metal scene’ doxa reproduction mechanism which accentuate three important values, namely authenticity, independency, and community. Finally, this three findings are the manifestation of extreme metal scene resistance towards state and market power in the neoliberal era. Tulisan ini berfokus pada praktik bermusik musisi metal ekstrem muda di Yogyakarta dalam konteks era neoliberal. Guna membangun pengetahuan sesuai dengan narasi musisi metal ekstrem muda, penelitian ini menggunakan pendekatan kualitatif, secara spesifik etnografi, antara April hingga Agustus 2019. Untuk mengartikulasikan dimensi konfliktual dan hierarkisitas skena metal ekstrem, penelitian ini menggunakan perspektif Bourdieusian. Adapun hasil analisis temuan lapangan menunjukkan bahwa, pertama, secara objektif, praktik bermusik musisi muda dimulai dalam kondisi dimana kesenjangan sosial telah eksis bahkan sebelum praktik tersebut terjadi. Hal ini menunjukkan karakteristik skena metal ekstrem sebagai ranah perjuangan yang bersifat hierarkis -terbentang dari leval lokal, nasional hingga global. Kedua, secara teoritis, praktik bermusik musisi muda dalam skena metal ekstrem membutuhkan dan mereproduksi kapital yang sangat spesifik terkait dengan rule of the game dalam skena tersebut, kami menyebutnya sebagai ‘kapital metal ekstrem’. Ketiga, muara dari proses akumulasi kapital metal ekstrem, kapital sosial dan kapital simbolik, serta proses embodiment mengenai kode-kode budaya terletak pada mekanisme reproduksi doxa skena metal ekstrem yang mengutamakan tiga nilai penting yaitu otentisitas, kemandirian dan komunitas. Adapun ketiga temuan tersebut merupakan manifestasi dari perlawanan skena metal ekstrem terhadap kuasa Negara dan pasar dalam era neoliberal